Takotsubo syndrome in New Zealand: current knowledge and future challenges. Issue 11 (31st August 2022) - Looi, Jen‐Li; Chan, Christina; Bridgman, Paul; Kerr, Andrew J.
Abstract: Takotsubo syndrome (TS), also known as apical ballooning syndrome, is a transient stress‐related cardiomyopathy characterised by acute but reversible left ventricular dysfunction. The condition tends to occur in postmenopausal women after a stressful event. At presentation, TS typically mimics acute myocardial infarction (MI) and the incidence of TS has been increasing worldwide. This is likely a consequence of an improved awareness of the existence of this syndrome and easier access to early echocardiography and coronary angiography. However, its aetiology remains poorly understood and it is probably still underdiagnosed. Similar to other countries, TS is being increasingly recognised in New Zealand. In this review, we discuss the demographics, clinical features and outcomes of patients with TS in New Zealand. Doing so informs us not only of the pattern of disease in New Zealand but it also provides insights into the condition itself.